1997
DOI: 10.1006/viro.1997.8793
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of a Functional Bovine Papillomavirus Type 1 Origin of Replication Reveals a Modular Tripartite Replicon with an Essential AT-Rich Element

Abstract: A functional replication origin was reconstituted using oligonucleotide cassettes corresponding to three sequence subelements within the Bovine Papillomavirus Type 1 (BPV-1) replication origin: the 23-bp AT-rich region (ATR), the 18-bp binding site for the viral replication initiator protein E1 (E1BS), and a binding site for the viral transcriptional transactivator and replication enhancer protein E2 (E2BS). Replication of the reconstituted origin depended on heterologous expression of both the E1 and E2 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Anti-E2 polyclonal antibodies supershifted E2E1-ori and E2-ori (lanes 4 and 6 compared with lanes 7 and 8), but only E2E1-ori was supershifted with anti-E1 antibody (lanes 9 and 10). A similar complex, which migrated slightly slower than E2E1-ori and was supershifted with anti-E1 and -E2 antibodies, formed with E1 and E2 on the probe with proximal E2 BS12 (X/12, lanes [12][13][14][15][16][17][18][19][20]. This most likely corresponds to the E1E2-ori complex described previously (22).…”
Section: Recruitment Of E1 To Ori By E2 At Distal Sites-bpv Orimentioning
confidence: 60%
“…Anti-E2 polyclonal antibodies supershifted E2E1-ori and E2-ori (lanes 4 and 6 compared with lanes 7 and 8), but only E2E1-ori was supershifted with anti-E1 antibody (lanes 9 and 10). A similar complex, which migrated slightly slower than E2E1-ori and was supershifted with anti-E1 and -E2 antibodies, formed with E1 and E2 on the probe with proximal E2 BS12 (X/12, lanes [12][13][14][15][16][17][18][19][20]. This most likely corresponds to the E1E2-ori complex described previously (22).…”
Section: Recruitment Of E1 To Ori By E2 At Distal Sites-bpv Orimentioning
confidence: 60%
“…5). The consensus E2 recognition sequence, ACCN 6 GGT (Androphy et al, 1987;Moskaluk & Bastia, 1987), is found in multiple copies in the LCR with at least one copy required within the minimal origin of replication (McShan & Wilson, 1997;Russell & Botchan, 1995;Ustav et al, 1993). The total number of E2 binding sites encoded varies between PV groups, in part as a reflection of subtle divergence in patterns of viral gene expression.…”
Section: E2 Transcriptional Modulatormentioning
confidence: 99%
“…Indeed, small molecule inhibitors of the herpes simplex virus (HSV) UL5 helicase have been described recently (Anonymous, 1996) which show antiviral activity when assayed in HSV-infected cells. An inhibitor of E1 would likely be broad-based, acting on most HPV types as the general mechanism of viral DNA replication is thought to be well conserved (Lu et al, 1993;McShan & Wilson, 1997;Remm et al, 1992;Russell & Botchan, 1995;Sverdrup & Khan, 1994;Ustav et al, , 1993. E1 and E2 can function to replicate plasmid DNA containing heterologous animal and human PV origins of replication, and heterologous mixes of E1 and E2 proteins will support origin-dependent PV replication (Chiang et al, 1992;Del Vecchio et al, 1992;Gopalakrishnan & Khan, 1994;Kuo et al, 1994;Zou et al, 1998).…”
Section: E1 Origin Binding Helicasementioning
confidence: 99%
“…In order to initiate viral DNA replication, the E1 protein forms a multimeric complex with the E2 protein, the viral origin of replication, and several host cell factors (2,6,8,13,15,26,28,33). The minimal BPV origin of replication is approximately 60 bp in length and contains, in order from 5Ј to 3Ј, a 23-bp AT-rich element, an 18-bp imperfect palindrome which serves as an E1 binding site, and a 12-bp palindromic E2 binding site (20).E1 functions as the initiator of papillomavirus DNA replication in vivo and plays several roles in this capacity. It is a multifunctional 68-kDa phosphoprotein which cooperates with the E2 protein to bind sequence-specifically to its cognate E1 binding element in the viral origin, facilitates origin DNA unwinding by acting as an ATP-dependent helicase, recruits the host cell DNA polymerase ␣-primase complex, which then begins de novo DNA synthesis, and interacts with regulatory host cell factors such as cyclin E (8, 18, 23, 28, 32, 38).…”
mentioning
confidence: 99%
“…In order to initiate viral DNA replication, the E1 protein forms a multimeric complex with the E2 protein, the viral origin of replication, and several host cell factors (2,6,8,13,15,26,28,33). The minimal BPV origin of replication is approximately 60 bp in length and contains, in order from 5Ј to 3Ј, a 23-bp AT-rich element, an 18-bp imperfect palindrome which serves as an E1 binding site, and a 12-bp palindromic E2 binding site (20).…”
mentioning
confidence: 99%